PENERAPAN METODE PROTOTYPING PADA PERANCANGAN APLIKASI SPPD KPPN MEDAN II BERBASIS WEBSITE - Crystal Jelita Lumban Tobing (Jurnal Teknologi Informasi Mura, 2019)
KPPN Medan II is one of the government organization units at the Ministry of Finance. Where leaders and employees who work at KPPN Medan II always carry out official trips between cities and outside the city. With these conditions, making SPPD documents experiencing the intensity of official travel activities carried out by employees of KPPN Medan II can be said frequently. So that in making SPPD in KPPN Medan II is still using the manual method that is recording through Microsoft Word which in the sense is less effective and efficient. In naming employees who get official assignments, officers manually entering employee data that receives official travel letters are prone to being lost because data is manually written. The web-based SPPD application is built by applying this prototyping method which is expected to facilitate SPPD KPPN Medan II management officers in making SPPD that is effective, efficient, accurate, time-saving, and not prone to losing SPPD data of KPPN Medan II employees who will has made official trips due to the existence of a special database to accommodate all SPPD files.